Vegetative propagation of 'GF 677' (P. persica x P. amygdalus) stone fruit rootstock - Du Toit, Jeanne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1995.